F141. Sensorimotor robotic measures of tDCS and HD-tDCS enhanced motor learning in children. (May 2018) - Cole, Lauran; Giuffre, Adrianna; Ciechanski, Patrick; Metzler, Megan; Carlson, Helen; Zewdie, Ephrem; Kuo, Hsing-Ching; Webber, Amy; Harris, Ashley; Kirton, Adam
Abstract : Introduction: Perinatal stroke causes hemiparetic cerebral palsy (CP) and lifelong disability. Treatments are limited but non-invasive brain stimulation, such as transcranial direct-current stimulation (tDCS) can alter cortical excitability, providing a unique opportunity for therapeutic neuromodulation in CP. We have demonstrated that application of tDCS can enhance motor skill acquisition in children. Growing evidence suggests that tDCS is safe in pediatrics, however refined forms of stimulation such as high-definition (HD)-tDCS have not been applied in children. The KINARM robot objectively quantifies sensorimotor function and holds potential to examine functional changes associated with tDCS-paired motor learning. We aimed to characterize changes in sensorimotor function induced by tDCS and HD-tDCS paired motor learning in children. We hypothesized that application of tDCS and HD-tDCS will improve motor function (visually-guided reaching; VGR), but only tDCS will improve sensory function (position matching). Methods: AMPED (Accelerated motor learning in pediatrics) is a randomized, sham-controlled trial (ClinicalTrials.gov: NCT03193580). Healthy, right-handed children (12–18y) were recruited. A validated 4-stage KINARM protocol and a series of motor function assessments [Purdue Pegboard Test (PPT), Jebsen Taylor Test, and Serial Reaction Time Task] were completed at baseline, post-training, and six weeks later. Participants were randomized to receive sham tDCS, anodal tDCS, or anodal HD-tDCS targeting the right primary motor cortex. Over five consecutive days, participants trained their left hand on the PPT during stimulation. Safety and tolerability was assessed daily. Group differences were explored using repeated measure ANOVA with post hoc correcting for multiple comparisons. Results: To date, 15 of 24 participants have completed the study (median 16.4y, range 12–18y, 67% female). Blinded interim analysis of cases grouped by intervention (group A, B, C) was performed on an exploratory basis. All participants improved their left hand PPT scores ( p < 0.001) regardless of intervention. The mean improvement in left hand PPT scores was 3.93 ± 1.33 pegs and was comparable across the groups: A 4.33 ± 1.78, B 3.08 ± 1.15, C 3.67 ± 1.18. No difference was observed between the groups. Right hand PPT scores increased (Group A p = 0.009) or were unchanged (both p > 0.06). Position matching performance did not change from baseline to post-training. Group A demonstrated improvements in left hand reaction (p = 0.03) and movement time (p = 0.04) in VGR tasks between baseline and post-training. All procedures were well tolerated with no adverse events reported. Conclusion: Application of tDCS and HD-tDCS in healthy children is safe, feasible, and tolerable. Sensorimotor function may be altered by tDCS and HD-tDCS paired with motor training. Optimizing tDCS and HD-tDCS protocols while exploring mechanisms of action is essential to advance therapeutic applications of tDCS in children with CP and other motor disabilities.